Os multiletramentos na formação do leitor : o hipertexto numa releitura crítica de textos da literatura sergipana - Fontes, Ana Cláudia Silva (2015)
This work discusses about reading and its new contexts of production and placement, as well as the contribution of digital literacy for the construction of meaning in literary text by the students of 9th grade in elementary school. It also tries to develop strategies for improving reading competence and critical understanding from the reading and analysis of texts in Sergipe’s literature, in order to exploit the linguistic identity and socio-cultural aspects of the region and thus make clear the importance of the act of reading in the expression of thought, social interaction and civic education. To develop these strategies, the use of IKT (Information and Knowledge Technology) is welcomed by aid analysis of excerpts from works and the production of hypertext, through hyperlinks, always valuing the creative process of the student and noting its critical positioning/understanding across the text. The theoretical basis of this TCF is based on Xavier (2002, 2013), Rojo (2012, 2013, 2015), Santaella (2007), Chartier (1998) and Aguiar and Bordini (1988). Thus, in the introduction, the reader is located in the selected theme; in the chapter on theoretical considerations, the focus is the text theories, reading, multiliteracy and Hypertext; in Chapter 3, the methodology will be outlined to in the next chapter, the educational notebook, be detailed and implemented; data analysis will be considered in Chapter 5; and to complete this research, concluding remarks are in Chapter 6. Hopefully, with this work, which students can achieve a satisfactory development of reading as a social practice, realizing its functionality from the language tags that are highlighted in the text and in their lines. Moreover, that enables educators, teaching new perspectives supported on new technologies as a means of motivation to practice teaching, extension to look for new forms of literacy, in which the student and his socio-historical context are necessary parts of action and which thus can bring resignifications to the text in its social use.